2017
DOI: 10.1080/16549716.2017.1410048
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stillbirths in Bangladesh: evidence from the 2004–2014 nation-wide household surveys

Abstract: Background: Globally, stillbirth remains a significant public health issue, particularly in developing countries such as Bangladesh. Objective: This study aimed to investigate the potential predictors of stillbirths in Bangladesh over a ten-year period. Methods: The Bangladesh Demographic and Health Surveys data for the years 2004, 2007, 2011 and 2014 (n = 29,094) were used for the study to investigate the predictors of stillbirths. Stillbirth was examined against a set of community, socio-economic and child c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
2
21
4
Order By: Relevance
“…Thus, aforementioned studies were conducted in referral hospitals which have better obstetric care facilities and skilled health workforce; whereas our study setting was a general hospital with fewer obstetricians and majority of cases were referred from peripheral primary health care units with poor facilities, which provide obstetric services for a predominantly rural population. The proportion of stillbirths in our nding was also higher than the global estimates of stillbirth for Ethiopia (25,26), and other studies from developing countries such as Bangladeshi (27) and India (28). This variation could be partly explained by differences in study settings and methods because the present study was a hospital based study unlike other community based studies from developing countries.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, aforementioned studies were conducted in referral hospitals which have better obstetric care facilities and skilled health workforce; whereas our study setting was a general hospital with fewer obstetricians and majority of cases were referred from peripheral primary health care units with poor facilities, which provide obstetric services for a predominantly rural population. The proportion of stillbirths in our nding was also higher than the global estimates of stillbirth for Ethiopia (25,26), and other studies from developing countries such as Bangladeshi (27) and India (28). This variation could be partly explained by differences in study settings and methods because the present study was a hospital based study unlike other community based studies from developing countries.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies have shown that an increase in maternal education could lead to a corresponding improvement in healthy behaviors such as the timely decision to seek appropriate medical care during pregnancy [26, 27]. Studies have also shown that a higher maternal education could also increase health service utilization such as antenatal care services which involves serologic screening for syphilis, iron-folic acid supplementation, malaria treatment and prophylaxis, diagnoses and treatment of asymptomatic bacteriuria, blood pressure monitoring, anti-tetanus immunization, and the prevention of mother-to-child transmission of human immunodeficiency virus (HIV) thereby leading to a reduction in stillbirth [28–31].…”
Section: Discussionmentioning
confidence: 99%
“…36 However, ongoing engagement provided entry points for the malaria intervention in Laos, and the flexibility of that intervention enabled issues of drinking water and other basic health care to be addressed. 35 Such integration goes beyond using local knowledge and perspectives of problems unavailable to high-level decision makers to improve information flows and delivery mechanisms for particular issues and provides the necessary platform for working toward UHC. 60 Other studies have also highlighted the need for a systemwide approach to community engagement rather than processes that are often ad hoc.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria Elimination in Laos A malaria elimination project combined elements of consultative and collaborative engagement. 35 Here, a predesigned package of interventions was presented to the community through existing community partners, but the engagement was required to promote uptake and adherence-primarily a consultative form of engagement. Ongoing discussions with the residents informed adaptations in the intervention to be responsive to the needs of the community-even beyond the focus on malaria elimination-a strategy that generated buy-in and enhanced the coverage of the treatment.…”
Section: Case Study Of Consultative/collaborative Engagement: Aborigimentioning
confidence: 99%
See 1 more Smart Citation